Autocuidado y prevención del pie diabético en el Club Amigos Dulces del Hospital General Isidro Ayora. Loja. - Valdivieso Espinoza, Rafael Ángel (2013)
With the realization of this research called "Self-care and prevention of diabetic foot in “Sweet Friends of General Hospital Isidro Ayora club" sought to know if self-care practices could influence the prevention of possible complications in the feet. For it were proposed three objectives: to determine the correlation between personal practices of prevention and self-care with diabetic foot neuropathy, comparing the effectiveness of self-care and prevention by gender and based on the findings develop a guide illustrated of self-care daily of foot and disseminate on-site research. This research is descriptive, qualitative and quantitative transversal, because this was identified through self-care practices that are used daily to keep your feet healthy and injury free. The universe were all diabetics and hypertensive diabetic club "Sweet friends" which made ​​control of their disease in General Hospital Isidro, and sample are fifty people who frequently attend all activities planned and developed within this. To meet the objectives, a home visit was conducted to gather information by conducting a survey, and also performed a physical examination of the feet, to assess the effectiveness of self-care at home. The found results show that there is some knowledge about foot care, but these are not enough to prevent injury to your feet develop. That is why it has developed a guide for daily foot care to be released in club "Sweet Friends" mediated dialogue and participation to achieve the empowerment of everyone.